2022
DOI: 10.22460/semantik.v11i1.p61-70
|View full text |Cite
|
Sign up to set email alerts
|

Pemanfaatan Media Canva Dan Aplikasi Quizizz Pada Pembelajaran Teks Fabel Peserta Didik SMP

Abstract: The use of technology in the learning process is an effort to encourage renewal so that the learning process becomes more effective. Utilization of technology in learning can be used in learning media. One of the uses of learning media that uses digital technology is the use of Canva and Quizizz applications. The purpose of this study is to describe the use of learning media assisted by the Canva and Quizizz applications in learning fable texts for junior high school students. The Canva application is a web-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
3

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 6 publications
0
4
0
3
Order By: Relevance
“…Canva media can be used by educators as an innovative learning media option combined with information from the internet about the material to be taught so that it not only provides study material but can also provide the latest information according to the material being taught (Hadana et al, 2023;Kartiwi et al, 2022). The learning media applied at SMP Negeri 5 Yogyakarta, especially classes VIII B and VIII E in advertising materials, slogans, and posters, proves that learning activities in the classroom are more communicative between teachers and students because students are interested in new things about the material by including advertisements that they often come across and they don't know what type of advertisement it is.…”
Section: Resultsmentioning
confidence: 99%
“…Canva media can be used by educators as an innovative learning media option combined with information from the internet about the material to be taught so that it not only provides study material but can also provide the latest information according to the material being taught (Hadana et al, 2023;Kartiwi et al, 2022). The learning media applied at SMP Negeri 5 Yogyakarta, especially classes VIII B and VIII E in advertising materials, slogans, and posters, proves that learning activities in the classroom are more communicative between teachers and students because students are interested in new things about the material by including advertisements that they often come across and they don't know what type of advertisement it is.…”
Section: Resultsmentioning
confidence: 99%
“…She added, "Once we choose the template, it is easy to customize and adjust it to our needs." Similarly, Kartika and Rostikawati (2022) found that Canva is a web-based design tool that allows users to create appealing designs using the various templates it provides. They added that Canva users can create various designs such as graphics, posters, presentations, flyers, and brochures.…”
Section: The Benefits Of Canva As a Tool To Create English Learning M...mentioning
confidence: 99%
“…It can increase students' interest and motivation by interestingly presenting teaching materials. Research by Kartiwi and Rostikawati (2022) supports Canva as a web-based design tool that allows for the creation of graphics, posters, presentations, flyers, and brochures.…”
Section: Benefits Of Canva Application As a Tool To Create English Le...mentioning
confidence: 99%
“…Saat kegiatan pembelajaran berlangsung, siswa hanya diberikan sedikit penjelasan materi serta contoh yang ada di dalam buku paket dengan materi sangat terbatas, sedangkan kegiatan pembelajaran harus dipersiapkan sebaik mungkin agar siswa memahami betul materi yang akan disampaikan. Salah satu yang perlu dipersiapkan guru dalam kegiatan belajar mengajar adalah media pembelajaran [4]. Supaya siswa dapat memahami konsep kimia dengan baik, maka proses pembelajaran tidak bisa dilakukan hanya sebatas teori yang lakukan dikelas saja, namun juga dibutuhkan suatu metode pembelajaran yang menuntut siswa untuk mengembangkan aspek kognitif dan psikomotoriknya [5].…”
Section: Pendahuluanunclassified